2021
DOI: 10.4081/gh.2021.997
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influence on <em>Triatoma vitticeps</em> occurrence and <em>Trypanosoma cruzi</em> infection in the Atlantic Forest of south-eastern Brazil

Abstract: Trypanosoma cruzi requires a triatomine insect vector for its life cycle, which can be complex in different enzootic scenarios, one of which is the unique transmission network in the Atlantic Forest of south-eastern Brazil. In Espírito Santo (ES) State, highly infected Triatoma vitticeps are frequently reported invading domiciles. However, triatomines were not found colonizing residences and mammals in the surrounding areas did not present T. cruzi infection. To date, the biotic and abiotic variables that modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Other studies have shown the presence of the triatomine species T. vitticeps in 27 municipalities of Espírito Santo, including localities neighboring Alegre and Iconha. More than 85% of the triatomines captured were infected with flagellates morphologically similar to T. cruzi 8 , 9 . Recently, molecular approaches confirmed the presence of the flagellate species T. cruzi infecting T. vitticeps and P. geniculatus from the Atlantic Forest in southeastern Espírito Santo, in regions such as Caparaó and Litoral Sul, which geographically encompass the municipalities of Alegre and Iconha 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown the presence of the triatomine species T. vitticeps in 27 municipalities of Espírito Santo, including localities neighboring Alegre and Iconha. More than 85% of the triatomines captured were infected with flagellates morphologically similar to T. cruzi 8 , 9 . Recently, molecular approaches confirmed the presence of the flagellate species T. cruzi infecting T. vitticeps and P. geniculatus from the Atlantic Forest in southeastern Espírito Santo, in regions such as Caparaó and Litoral Sul, which geographically encompass the municipalities of Alegre and Iconha 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The state of Espírito Santo, Brazil, has a low incidence of autochthonous human cases originating from infected sylvatic triatomine bugs in an epidemiological scenario wherein Triatoma vitticeps exhibits highest rate of natural infection, mainly attributed to its close relationship with wild mammals not refractory to T. cruzi 8 , 9 . In 2012, a fatal acute case of 2-year-old was reported after accidental oral ingestion of one T. cruzi -infected triatomine in Rio da Prata, a rural area of Guarapari 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of this geographic filter to generate the pseudo-absence points in this area C -O around each occurrence allows a significant improvement in the results [33]. The T. vitticeps exclusion buffer radius was 10 km [34], while its inclusion buffer was 60 km, approximately 90% of the median of the matrix of distances between occurrences. The exclusion buffer for P. megistus was the same as for T. vitticeps, while the inclusion buffer, due to its greater environmental diversity because of its greater spatial distribution along the Atlantic Forest, was defined as being 40% more than median of the matrix of distances between occurrences of T. vitticeps.…”
Section: Ecological Niche Modelingmentioning
confidence: 99%